2009
DOI: 10.1136/jnnp.2009.185348
|View full text |Cite
|
Sign up to set email alerts
|

A randomised, double-blind, placebo-controlled study of topiramate in the treatment of Tourette syndrome

Abstract: This double-blind, placebo-controlled trial provides evidence that topiramate may have utility in the treatment of moderately severe TS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
84
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(90 citation statements)
references
References 11 publications
(7 reference statements)
3
84
0
3
Order By: Relevance
“…131 In this study, 29 adults and children were randomised to maximum dose of 200 mg/day topiramate or placebo for 6 weeks. Because the mean age of this population was low (16.5 years, SD 9.9), it was assumed that the majority of the participants would be < 18 years and this study was combined with the child studies in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…131 In this study, 29 adults and children were randomised to maximum dose of 200 mg/day topiramate or placebo for 6 weeks. Because the mean age of this population was low (16.5 years, SD 9.9), it was assumed that the majority of the participants would be < 18 years and this study was combined with the child studies in the meta-analysis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…For the study of topiramate, 131 a computer-generated randomisation code was used but the presence of allocation concealment was unclear. There was assurance of blinding of participants, providers and outcome assessors.…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Доступные в Российской Федерации основные лекарственные средства для лечения ХТ и СТ, указанные в Европейских рекомендациях [40]. данным двойного слепого плацебо-контролируемого ис-следования с участием 29 пациентов с СТ, топирамат ока-зался эффективным и безопасным средством при лечении среднетяжелых и тяжелых форм СТ [44]. В открытом ис-следовании леветирацетама у 60 детей с СТ показано сни-жение выраженности тиков на 20% по Йельской глобаль-ной шкале тяжести тиков и улучшение по шкале общего клинического впечатления.…”
Section: журнал неврологии и психиатрии 1 2015unclassified
“…A small clinical trial indicated that the antiepileptic agent that influences excitatory and inhibitory neurotransmission, topiramate, is effective for tics [22]. This drug can cause language and other cognitive side effects which might interfere with a child's learning.…”
Section: Other Medicationsmentioning
confidence: 99%